Factor-Market Rivalry - Markman, Gideon D.; Gianiodis, Peter T.; Buchholtz, Ann K. (Academy of Management Review, 2009)
With its focus on product-market rivalry, competitive dynamics research fails to tell the whole story. We develop a theory of factor-market rivalry to shed light on atypical rivals and competitive blind spots. Focusing on resource versatility and mobility, the theory introduces dynamic constructs—resource discontinuities, leapfrogging, and captivity—and explains their role in triggering cascading effects. To illustrate the theory's conceptual utility, we apply the concepts of factor-market rivalry to mutual forbearance in multimarket competition.